2009
DOI: 10.1007/s10654-009-9397-9
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling and the epidemiological research process

Abstract: The authors of this paper advocate for the expanded use of mathematical models in epidemiology and provide an overview of the principles of mathematical modeling. Mathematical models can be used throughout the epidemiological research process. Initially they may help to refine study questions by visually expressing complex systems, directing literature searches, and identifying sensitive variables. In the study design phase, models can be used to test sampling strategies, to estimate sample size and power, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Although disease modelling is not a novel issue,8 the use of validated multivariate predictive models with high accuracy and established ability to discriminate risk may be of particular interest for health promotion planners and public health policy makers 9 10…”
Section: Introductionmentioning
confidence: 99%
“…Although disease modelling is not a novel issue,8 the use of validated multivariate predictive models with high accuracy and established ability to discriminate risk may be of particular interest for health promotion planners and public health policy makers 9 10…”
Section: Introductionmentioning
confidence: 99%
“…The primary outcome was persistent disability at 6 months, measured using the modified Disabilities of the Arm, Shoulder and Hand questionnaire (range 0-11). Outcome was dichotomised, with poor outcome defined as any disability (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) Background: How patients with comorbidities are treated in daily practice is unknown. Understanding the decision making process of physical therapists (PTs) and exploring the treatment of comorbid patients in daily practice might be a first step to unravel the complexity of treating multi-diseased patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results underscore the importance of lifestyle by showing the effects associated with obesity on lifetime risk of type 2 diabetes. 9 Research Program for Diabetes and obesity, University of Helsinki; 10 Folkhalsan Research Center, Finland; Corresponding author's e-mail: bahareh.rasouli@ki.se Aim: Smoking is associated with an increased risk of type 2 diabetes. It has been suggested that smoking may reduce the risk of LADA, possibly through modulating immune response, but few studies have addressed this issue.…”
Section: Abstract #: O 69mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the transmission characteristics of infectious diseases in communities, regions, and countries can lead to better approaches to the control of such diseases. Mathematical models are used in comparing, planning, implementing, evaluating, and optimizing various detection, prevention, therapy, and control programs [14,4].…”
Section: Introductionmentioning
confidence: 99%